Her juggling act : a working woman's dilemma - Chan, Carol Yan Ru (2012)
This report will detail on an initiative to promote awareness for the lack of work-life balance of working women in Singapore. The campaign was conceptualized and executed to raise the awareness of the struggles and difficulties working women in Singapore face today. Through the celebration of women’s contributions and achievements, we will also highlight further efforts that should be taken for women to move towards a healthier juggle between work and life, as well as to provide inspiration for young women who have yet to enter the workforce. With International Women’s Day celebrated annually in the month of March, the campaign’s main event, ILoveFit 2012, takes place on 24th and 25th March, in commemoration of International Women’s Day through sports and fitness.